Pelatihan Pertolongan Pertama pada Keluarga untuk Meningkatkan Kesiapsiagaan Gawat Darurat di Lingkungan Rumah - Zaenal, Zaenal; Mesa, Nofita Dewi Kok; Achmad, Viyan Septiyana; Noviar, Rizki Andita; Aryadi, Anggi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Emergency situations can occur anytime and anywhere, including in the home environment. Unfortunately, not all family members have the basic knowledge and skills to provide first aid before medical assistance arrives. The purpose of this community service activity is to improve family preparedness in dealing with emergencies through first aid training. The activity methods include counseling, practical training, and evaluation before and after the activity. The activity was carried out in RW 05, Sukamaju Village, Bandung City, involving 30 participants from family representatives. The results showed an increase in participants' knowledge and skills regarding first aid after training. This activity is expected to be the first step in forming a family that is alert and responsive in dealing with emergencies at home.